2011
DOI: 10.3390/rs3050878
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing of Mangrove Ecosystems: A Review

Abstract: Mangrove ecosystems dominate the coastal wetlands of tropical and subtropical regions throughout the world. They provide various ecological and economical ecosystem services contributing to coastal erosion protection, water filtration, provision of areas for fish and shrimp breeding, provision of building material and medicinal ingredients, and the attraction of tourists, amongst many other factors. At the same time, mangroves belong to the most threatened and vulnerable ecosystems worldwide and experienced a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
363
1
42

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 602 publications
(457 citation statements)
references
References 146 publications
4
363
1
42
Order By: Relevance
“…With 18% of the region's mangrove cover, deforestation rate in this country (1.1 and 0.6%) exceeded the South American average (0.69 and 0.18%) in estimates for 1980-1990 and 2000-2005. These figures may be more variable and dramatic at a subcountry level, bearing in mind that coarse-scale inventories using satellite imagery tend to overestimate mangrove cover due to low spatial resolution and heavy cloud cover (as observed in many areas of the Pacific coast and the Urabá region in the Caribbean coast) [14].…”
Section: Introductionmentioning
confidence: 99%
“…With 18% of the region's mangrove cover, deforestation rate in this country (1.1 and 0.6%) exceeded the South American average (0.69 and 0.18%) in estimates for 1980-1990 and 2000-2005. These figures may be more variable and dramatic at a subcountry level, bearing in mind that coarse-scale inventories using satellite imagery tend to overestimate mangrove cover due to low spatial resolution and heavy cloud cover (as observed in many areas of the Pacific coast and the Urabá region in the Caribbean coast) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Significant differences between each country's estimates are apparent. These discrepancies in part reflect the difficulties in arriving at accurate estimates through mapping (Heumann, 2011;Kuenzer et al, 2011). By 1999 it was suggested that certain Latin American countries had lost up to 40% of their total mangrove area (Lacerda and Schaeffer-Novelli, 1999).…”
Section: Change In Mangrove Extentmentioning
confidence: 99%
“…Reviews on the remote sensing of other forest ecosystems were provided by Malingreau (1992). Reviews on the remote sensing of coastal mangrove ecosystems have been published by Kuenzer et al (2011) and Blasco et al (1998). Rundquist, Narumalani, and Narayanan (2001), Henderson and Lewis (2008), Lawler (2001), and Kuenzer and Knauer (2013) published overarching articles on remote-sensing techniques for assessing further natural and agricultural wetland ecosystems, and Zhang et al (1997) focused on remote sensing for saltmarsh ecosystems.…”
Section: Spaceborne Remote Sensing Of Vegetation Biodiversitymentioning
confidence: 99%